The Subaltern Can Speak: Voices of Poets in Divided Korea - Ailee Cho (Journal of Global Initiatives, 2011)
Spivak asks, "Can the Subaltern Speak?" and answers in the negative. The same question can be asked of South Korea following its liberation from Japanese colonial rule. But the answer is in the positive. Subaltern's voices can be heard in the poems on the division of Korea. Here, divided Korea is compared to a severed human body in deep pain as if an actual human body had been severed. It is also represented as an unnatural state that will end in apocalyptic vision. When readers return to the origin of the national division and empathize with the body in pain, this voice still remains alive.